The role of myeloid cells in HIV associated immune reconstitution inflammatory syndrome - Wilkinson, Robert; Meintjes, Graeme (Henry Stewart Talks, 2012)
TB-immune reconstitution inflammatory syndrome (IRIS) is a common complication of combined antitubercular and antiretroviral therapy, The two forms of IRIS: paradoxical and unmasking, Lack of a diagnostic test for TB-IRIS, Expansion of Interferon gamma secreting T cells is associated with TB-IRIS, Multiple cytokines are elevated in TB-IRIS, many of myeloid origin, Benefits of adjunctive corticosteroid therapy in TB-IRIS, Steroid therapy reduces the levels of IL-6, IL-10, IL-12p40, TNF, Interferon-gamma and CXCL-10 in TB-IRIS patients, Suppurative necrosis may occur in TB-IRIS, implying a role for neutrophils, Evidence of a prominent role for myeloid cells in the pathogenesis of TB-IRIS